1999
DOI: 10.1159/000022873
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Variation in the Mitochondrial Targeting Sequence Polymorphism of MnSOD

Abstract: In contrast to CuZn superoxide dismutase (SOD), only a very limited number of mutations have been described in MnSOD. One interesting example is a polymorphism (Ala-9Val) in the mitochondrial targeting sequence of this radical-scavenging enzyme. We have studied the Ala-9Val polymorphism in various ethnic groups by means of the oligonucleotide ligation assay. There were significant variations in this unique polymorphism between three different language groups: Baltic (Lithuanians), Finnic (Finns and Saamis) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 15 publications
4
15
0
Order By: Relevance
“…A unique Ala-9Val variant has been identified that alters the targeting of the enzyme to the mitochondria [28,29]. Interestingly, population studies have shown that the heterozygote of the SNP to be the most common genotype in all populations surveyed [30]. The effects of the Ala-9Val are not fully understood and therefore it is difficult to hypothesize as to the effects of the variant on the risk of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…A unique Ala-9Val variant has been identified that alters the targeting of the enzyme to the mitochondria [28,29]. Interestingly, population studies have shown that the heterozygote of the SNP to be the most common genotype in all populations surveyed [30]. The effects of the Ala-9Val are not fully understood and therefore it is difficult to hypothesize as to the effects of the variant on the risk of preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…SOD2 Ala16Val is a dimorphism caused by a C to T transition, which results in Ala to Val substitution at the À9 position of the mature SOD2 isozyme. Previous studies have shown that the Ala allele frequency in Caucasian populations is around 0.5 (0.47-0.56) [14][15][16][17][32][33][34], whereas in African populations it is a little lower (0.36) (data from the international HapMap project), and in Asian populations is the lowest (0.12-0.36) [29,35,36]. Our results for German (0.548), Japanese (0.128) and Xhosa (0.415) populations were in good agreement with these studies.…”
Section: Nucleic Acidsmentioning
confidence: 99%
“…18 In this latter population, the alanine variant of Mn-SOD has been associated with an increased risk of breast cancer in premenopausal women,19,20 sporadic motor neurone disease,21 diabetic nephropathy,22 and ALD,5 whereas the association with Parkinson's disease, first observed in the Japanese," has not been confirmed in a subsequent study performed in Germany. 23 In contrast to the French study, we found no association between the alanine-Mn-SOD allele and advanced ALD in our cohort of 499 patients.…”
Section: Discussionmentioning
confidence: 95%